Defending corner kicks in the English Premier League: near-post guard systems - Pulling, C.; Newton, J. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to investigate the use of near-post guard systems when defending corner kicks in the English Premier League during the 2015/2016 season. A total of 750 corner kicks from 79 English Premier League matches were analysed. There were a total of eight different near-post guard systems observed. Only six corner kicks (0.8%) were observed where there was no guard positioned in the near-post area when defending corner kicks. The one-one system only conceded one goal from 148 corner kicks (0.7%) observed, whereas the one-zero system conceded 8 goals from 159 corner kicks (5.0%) observed. However, when all attempts at goal were included, there was no significant association between the different near-post guard systems and the number of attempts at goal (p > 0.05). An important finding was that there were 236 defensive clearances performed by the guards from the 750 corner kicks that were analysed (31.5%), this suggests that these defensive players play an important role in preventing the attacking team from having an attempt at goal from a corner kick. Further research on corner kicks is still required and suggestions have been made for future investigations.